Pilot-scale depuration demonstrates the suitability of non-pathogenic Vibrio parahaemolyticus as a surrogate for commercial-scale validation studies - Spencer L. Lunda; Samantha Kilgore; Jennifer M. Hesser; Joy G. Waite-Cusic; Carla B. Schubiger (PLoS ONE, 2025)
Shellfish producers have proposed using depuration systems to reduce Vibrio parahaemolyticus levels by supporting the oysters’ natural purging ability. For commercial viability, depuration efficacy must be validated in relevant species and at scale using appropriate conditions, including time and temperature. This study aims to I) compare depuration efficacy across oyster species, II) assess non-pathogenic V. parahaemolyticus as a surrogate, and III) optimize pilot-scale depuration to identify process variables likely to achieve >3.0-log reduction of V. parahaemolyticus at commercial-scale. Three oyster species (Crassostrea gigas, Crassostrea sikamea, Crassostrea virginica) were exposed to artificial seawater (35 ppt) containing five non-pathogenic or five pathogenic V. parahaemolyticus strains. Inoculated oysters were placed in a pilot-scale recirculating depuration system at 5, 11, or 13 °C for 7 days. Three replicate depuration trials were conducted, sampling five oysters per species and the two different bacterial inoculations every 24 hours. V. parahaemolyticus in oyster tissue was enumerated using serial dilutions and spread plating techniques on Thiosulfate-Citrate-Bile Salts-Sucrose agar. In C. gigas and C. sikamea, inoculation achieved at least a 5 log CFU/g V. parahaemolyticus, but C. virginica did not consistently reach target density within 24 hours. Accumulation of non-pathogenic and pathogenic strains was similar across species. Depuration at 11°C achieved a > 3 log CFU/mL reduction of the pathogenic strain combination in C. gigas and C. sikamea tissues within five days, while C. virginica averaged 2.8 log CFU/mL. V. parahaemolyticus clearance rate was rapid during the first 24–48 hours of depuration. The non-pathogenic V. parahaemolyticus strain combination was reduced at a comparable or slower rate than the pathogenic combination, supporting its suitability as a surrogate for commercial validations. These findings support depuration as an effective V. parahaemolyticus mitigation strategy in live oysters; though optimization of parameters, including temperature and duration, is needed to meet reduction targets in all species.